Application of Random Amplified Polymorphic Analysis for the Detection Genetic Variation in Tomato (Lycopersicon Esculentum Mill.) - Qassar, Iyad; Ahmad, Narmeen S; Ibrahim, Kadhim M (Al-Nahrain Journal of Science, 2018)
This study was carried out to induce variations in tissue cultures of tomato (Lycopersicon esculentum Mill.) by using physical (gamma radiation) and chemical (sodium azide) mutagens. Different plant growth regulators were tested for their potentials in callus induction, and shoot and root formation. Callus initiation on hypocotyl explants was achieved on Murashige and Skoog’s (MS) medium supplemented with 0.1 mg/l 2, 4-dichlorophenoxyacetic acid (2, 4-D) and 0.5 mg/l 6-benzyl-aminopurine (BAP). Shoot regeneration was performed using hypocotyl explants cultured on MS medium containing 0.8 mg/l indole-3-acetic acid (IAA) and 2.0 mg/l BAP. Rooting was achieved on MS medium supplemented with 0.4 mg/l IAA. Callus cultures and seedlings were irradiated with gamma radiation at six doses 5, 15, 25, 35, 45 or 55 mGy from 137Cs source, or treated with sodium azide(SA) at four concentrations 0.5, 1.0, 2.0 or 3.0 mM for 1, 3 or 6 hours. Callus fresh weights were increased after irradiation with 25 mGy gamma rays and treatment with (0.5 or 3.0) mM SA for 1 hour. Shoot regeneration was observed in all irradiated hypocotyl explants. Shoot regeneration at (15 and 35) mGy was similar to the control. Root formation was observed on hypocotyls irradiated with low doses (5 or 15) mGy only, while SA inhibited shoot and root regeneration. Random amplified polymorphic DNA (RAPD) technique was performed todetect genetic mutation in extracted DNA samples. DNA was extracted from mother plant, callus tissue, irradiated calli with 15 or 45 mGy of gamma ray and calli treated with 0.5 and 3 mM SA. Twelve arbitrary 10-mer primers were used of which eight primers gave amplification products. The total number of amplification products was 27 bands, of which 22 bands were monomorphic bands which indicates the presence of genetic mutations. One of these primers, C-02, revealed polymorphism in callus tissues treated with 45 mGy of gamma radiation, 0.5 and 3.0 mM SA. Others primers, C-08 and C-09, revealed polymorphisms in irradiated callus tissues with 15 mGy gamma radiation. RAPD was found to be effective technique to detect genetic mutations in callus tissue.